Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content:1. The Degree of Using Infographics in Presenting & Presenting data in Public Education Agency Programs from General Supervisors’ Perspective in the Ministry of Education in The Kingdom of Saudi ArabiaMrs. Wardah Ali H. Al-Razouq , Prof. Ajlan Mohammed H. Al-Shehri2. Level of Including Values in Arabic Language Course for 3G Primary, in the Kingdom of Saudi Arabia, in Light of the Cross-Cutting Dimensions of the Public Education Curricula StandardsMrs. Taghreed Saeed Al-Rasasimah, Co-Prof. Abeer Mohammed Al-Arfaj3. The Impact of Electronic Educational Broadcasting on the Development of English Listening Skills for Primary Students Sixth GradeMrs. Seetah Mohammed Abdullah Al-Sahali, Prof. Ajlan Mohammed Al-Shehri4. The Effectiveness of Instructional Scaffolding Strategy in Developing Social Interaction of Eleventh-Grade Students in The Subject of HistoryDr. Sattar Jabbar Haji, Dr. Imad Ali Safar , Asst-Lecturer \ Dilkhaz Shekhomar Mostafa5. The Degree of Possessing E-Learning Skills by Secondary Stage Teachers from School Principals’ Perspectives in Amman GovernorateMrs. Hasnah Abdel-Hafeez Al-Ashush6. Attitudes of teachers and students' guardians towards the application of the "Trimester" in The Kingdom of Saudi ArabiaMrs. Najwa Mohammed A. Al-Shammari7. A Literature Review on Fostering Teaching English as Foreign Language (EFL) Using Digital ActivitiesMrs. Faten Ahmed Saeed Alghamdi , Co-Prof. Mai Mohammed Lutfi Alnajami
Keywords: Journal of Curriculum and Teaching Methodology